Coupled Chemo-Mechanical Simulation of Geosynthetic-Reinforced Subgrades: A Critical Review of Computational Models and Predictive Methods - Nur Rasfina, Mahyan; Mastura, Azmi; Fauziah, Ahmad; Siti Noor Linda, Taib (Springer Nature, 2026)
The durability and resilience of geosynthetic-reinforced subgrades are increasingly threatened by coupled environmental and mechanical stressors, particularly in infrastructure systems exposed to cyclic traffic loads and chemically aggressive conditions such as acid rain, landfill leachates, and saline intrusion. This review provides a critical and systematic synthesis of current research on the chemo-mechanical behavior of reinforced subgrades, with an emphasis on the computational modeling approaches used to simulate their long-term performance. Particular attention is given to finite element models, damage mechanics frameworks, and multi-physics coupling techniques that capture the synergistic deterioration mechanisms arising from chemical degradation and repeated loading. The analysis compares behavior in homogeneous and layered soil systems, emphasizing the complexities of interface interactions, load transfer mechanisms, and degradation pathways of geosynthetics in soil. Current experimental protocols for chemical aging and mechanical testing are reviewed to assess their role in calibrating and validating numerical models. Despite growing interest in coupled modeling, significant gaps remain in integrating chemical transport, time-dependent material degradation, and dynamic loading into unified predictive frameworks. This paper further explores the potential of machine learning-assisted surrogate models, multi-scale simulations, and lifecycle-based computational strategies to support the design of resilient infrastructure. By bridging experimental insights with advanced numerical tools, this review advances the development of sustainable and adaptive ground reinforcement systems, aligning with the objectives of computational engineering and global infrastructure resilience goals.